THE EFFECT OF USING ROLE PLAYING STATEGY ON STUDENTS’ ACHIEVEMENT IN SPEAKING ENGLISH AT SMP MUHAMMADIYAH 01 MEDAN - Rahmawati Wati (BASIS (Bahasa dan Sastra Inggris), 2019)
This research entitled "The Effect of Using Role Playing Strategies on the ability to speak English at Muhammadiyah Middle School 01 Medan. This research was appointed to increase the courage of students to speak English using the "Role Playing" strategy. Then look for self-confidence efforts for students who speak English through the "Role Playing" strategy. Finally, to create the benefits of "Role Playing" in supporting English learning at Muhammadiyah Middle School 01 Medan. This research used descriptive quantitative and qualitative research methods. Quantitative methods to calculate the average value of student test results, while qualitative is used to calculate the observation results of student learning activities in each cycle. Everything was explained according to the facts found in the field during the research. The method used in data collection was the experimental method. The experimental method was a method of directly testing the effect of variables on other variables and testing the hypothesis of a causal relationship. The technique used in this method, namely by comparing classes that get special treatment and classes that do not get treatment.